ENVIRONMENTAL AUDIT: AN COMPANY’S OBLIGATION OR NECESSITY - Moh. Faisol; Nur Fadjrih Asyik; Wahidahwati (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2026)
This article aims to explore the position of environmental auditing from the perspective of a corporate obligation or need. The method used is a conceptual study based on an analysis of the underlying theory of environmental audits in companies. The results of the analysis and study stated that (1) environmental audits are seen as a corporate obligation that must be fulfilled both legally and morally; and (2) environmental audits are a need for the company's